Vous êtes sur la page 1sur 3

𝟐𝟓 − (𝒙 + 𝟏)𝟐

𝐥𝐢𝐦 √
𝒙→𝟒 𝟓 + (𝒙 + 𝟏)

SOLUCION

25 − (𝑥 + 1)2 (5 + (𝑥 + 1))(5 − (𝑥 + 1))


lim √ = lim √
𝑥→4 5 + (𝑥 + 1) 𝑥→4 5 + (𝑥 + 1)

25 − (𝑥 + 1)2
lim √ = lim √5 − (𝑥 + 1)
𝑥→4 5 + (𝑥 + 1) 𝑥→4

25 − (𝑥 + 1)2
lim √ = √5 − (4 + 1)
𝑥→4 5 + (𝑥 + 1)

25 − (𝑥 + 1)2
lim √ =0
𝑥→4 5 + (𝑥 + 1)

𝒕𝟐 − 𝟗
𝐥𝐢𝐦
𝒕→𝟑 𝒕𝟐 − 𝟓𝒕 + 𝟔

𝑡2 − 9 (𝑡 − 3)(𝑡 + 3)
lim = lim
𝑡→3 𝑡 2 − 5𝑡 + 6 𝑡→3 (𝑡 − 3)(𝑡 − 2)

Simplificamos
𝑡2 − 9 (𝑡 + 3)
lim 2
= lim
𝑡→3 𝑡 − 5𝑡 + 6 𝑡→3 (𝑡 − 2)

Evaluamos:
𝑡2 − 9 (3 + 3)
lim 2 =
𝑡→3 𝑡 − 5𝑡 + 6 (3 − 2)
𝑡2 − 9
lim =6
𝑡→3 𝑡 2 − 5𝑡 + 6
𝐥𝐢𝐦 √𝟑𝒙 + 𝟐 − 𝒙
𝒙→∞

SOLUCION

√3𝑥 + 2 + 𝑥
lim √3𝑥 + 2 − 𝑥 = lim √3𝑥 + 2 − 𝑥 ∗
𝑥→∞ 𝑥→∞ √3𝑥 + 2 + 𝑥
(3𝑥 + 2) − 𝑥 2
lim √3𝑥 + 2 − 𝑥 = lim
𝑥→∞ 𝑥→∞ √3𝑥 + 2 + 𝑥
−𝑥 2 + 3𝑥 + 2
lim √3𝑥 + 2 − 𝑥 = lim
𝑥→∞ 𝑥→∞ √3𝑥 + 2 + 𝑥
−𝑥 2 + 3𝑥 + 2
lim √3𝑥 + 2 − 𝑥 = lim 𝑥2
𝑥→∞ 𝑥→∞ √3𝑥 + 2 + 𝑥
𝑥2
3 2
−1 + 𝑥 + 2
lim √3𝑥 + 2 − 𝑥 = lim 𝑥
𝑥→∞ 𝑥→∞ √3𝑥 + 2 1
+𝑥
𝑥2
3 2
−1 + 𝑥 + 2
lim √3𝑥 + 2 − 𝑥 = lim 𝑥
𝑥→∞ 𝑥→∞ 3𝑥 + 2
√ 4 +1
𝑥 𝑥
3 2
−1 + 𝑥 + 2
lim √3𝑥 + 2 − 𝑥 = lim 𝑥
𝑥→∞ 𝑥→∞
√ 33 + 24 + 1
𝑥 𝑥 𝑥
Evaluando
3 2
−1 + ∞ + 2
lim √3𝑥 + 2 − 𝑥 = ∞
𝑥→∞
√ 33 + 24 + 1
∞ ∞ ∞
−1
lim √3𝑥 + 2 − 𝑥 =
𝑥→∞ 0
Esto nos indica que no hay ninguna técnica que quite la forma indeterminada, por
tanto:

lim √3 ∗ ∞ + 2 − ∞ = −∞
𝑥→∞
𝒔𝒆𝒏𝟑𝜽
𝐥𝐢𝐦
𝜽→𝟎 𝟐𝜽

𝑠𝑒𝑛3𝜃 1 𝑠𝑒𝑛3𝜃
lim = lim
𝜃→0 2𝜃 2 𝜃→0 𝜃

𝑠𝑒𝑛3𝜃 3 𝑠𝑒𝑛3𝜃
lim = lim
𝜃→0 2𝜃 2 𝜃→0 3𝜃

Haciendo 𝑥 = 3𝜃
Si 𝜃 → 0 si y solo si 𝑥 → 0

𝑠𝑒𝑛3𝜃 3 𝑠𝑒𝑛𝑥
lim = lim
𝜃→0 2𝜃 2 𝑥→0 𝑥
Como sabemos:
𝑠𝑒𝑛𝑥
lim =1
𝑥→0 𝑥

Entonces:
𝑠𝑒𝑛3𝜃 3
lim = (1)
𝜃→0 2𝜃 2

𝑠𝑒𝑛3𝜃 3
lim =
𝜃→0 2𝜃 2